Hematological status of rats (Rattus norvegicus L.) in the lactation period after giving supplements organic quail eggs - Basri, Hasan; Rini Saraswati, Tyas; Isdadiyanto, Sri (International Journal of Biological Research, 2018)
Organic quail eggs contain high nutrients and low cholesterol, so it is needed in the process of hematopoiesis that occurs in the bone marrow. The purpose of this study was to determine hematological status of rat (Rattus norvegicus L.) in the period of lactation after supplementation of organic quail eggs. This study is an experimental study using a completely randomized design with 4 treatments and 5 replications. Some treatments applied are: T0: Control; T1: The lactation period of (Rattus norvegicus L.) with giving quail eggs supplement of commercial feed; T2: The lactation period of (Rattus norvegicus L.) with giving quail eggs supplement of standard organic feed; T3: The lactation period of (Rattus norvegicus L.) with giving quail eggs supplement of given organic feed. The results showed that feed intake, weight femur, long bone of the femur, erythrocytes, and hemoglobin levels were not significantly different (p > 0.05), blood pH significantly different (p < 0.05). Supplementation of organic quail eggs could be maintain the condition hematological status of erythrocytes, hemoglobin and blood pH in the lactation period of (Rattus norvegicus L.).